Investigation of bioactive compounds and antimicrobial sensitivity of pawpaw (Carica papaya) leave extracts against morbific micro-organisms - O I Ogidi; P. S. Tobia; D. N. Ijere; U. M. Akpan; O. Omu; H. E. Carbom; A. R. Iyosayi (Creative Pharma Assent, 2022)
Pawpaw (Carica papaya) is a notable plant due to its medicinal benefits used globally to treat diseases which include dengue, malaria, inflammation, and skin infections. This study was aimed at investigating the bioactive compounds and antimicrobial sensitivity of Pawpaw (Carica papaya) leave extracts against morbific micro-organisms. The bioactive compounds of C. papaya leaves were analyzed using Chemical Standard techniques as reported in literatures and antimicrobial assay was done using agar well diffusion techniques. Qualitative phytochemical screening results of pawpaw leaves shows the presence of glycosides, tannins, flavonoids, steroids, saponins and terpenoids. The antimicrobial sensitivity result reveals higher zones of inhibition of methanolic extract against Staphylococcus sp (11.4±0.3 mm), Vibrio sp (10.3±0.2 mm), E. coli (9.7±0.3 mm), Shigella sp (9.1±0.3 mm), Yeast (9.1±0.3 mm) and Penicillium sp (8.3±0.4 mm). While aqueous extract shows higher zone of inhibition against Mould (8.0±0.5 mm). This study revealed pawpaw leaves contains secondary metabolites (bioactive compounds) while the antimicrobial sensitivity against the microorganisms explains the possibility of using the leaves as antibiotic substances (antimicrobial agents). Therefore, pawpaw leaves could be a significant source of medicine for the treatment of various fungal and bacterial infections.